2022
DOI: 10.1002/da.23255
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulant use and clinical outcome of repetitive transcranial magnetic stimulation treatment of major depressive disorder

Abstract: Background: Repetitive transcranial magnetic stimulation (rTMS) is an effective treatment for major depressive disorder (MDD). Psychostimulant medication use may be associated with improved rTMS outcomes, but a detailed understanding of these relationships is lacking. Methods:We compared MDD subjects taking psychostimulants (n = 37) with those not taking one of these medications (n = 53) during a course of 30 rTMS treatments.Changes in the 30-item Inventory of Depressive Symptomatology Self Report (IDS-SR30) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…In this study, rTMS was administered to MDD patients on the basis of oral escitalopram tablets. The results showed a total effective rate of 95.0%, similar to the study by Wilke et al, [ 15 ] indicating that rTMS can further improve the efficacy and alleviate symptoms in the treatment of MDD patients. RTMS is a type of physical therapy that was first proposed in 1985 and found to stimulate both the brain and nerves.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, rTMS was administered to MDD patients on the basis of oral escitalopram tablets. The results showed a total effective rate of 95.0%, similar to the study by Wilke et al, [ 15 ] indicating that rTMS can further improve the efficacy and alleviate symptoms in the treatment of MDD patients. RTMS is a type of physical therapy that was first proposed in 1985 and found to stimulate both the brain and nerves.…”
Section: Discussionsupporting
confidence: 86%
“…Functional areas such as the prefrontal cortex and subcortical cingulate gyrus are closely related to human emotional management and are common functional disorders in patients with depression. [ 15 , 16 ] Transcranial magnetic stimulation therapy can stimulate this area, activate specific neural circuit activities, and achieve the effect of regulating the emotional state of the brain and improving the emotional status of patients. [ 16 , 17 ] In addition, a large number of animal model studies in recent years have shown that rTMS is similar to antidepressants in the treatment of depression, and can promote the formation of hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The final set of sixteen studies (half open-label and half randomized controlled trials) investigated administering TMS in conjunction with stable doses of ongoing medications. Seven out the eight randomized controlled trials found that adding TMS on top of stable ongoing medications can reduce MDD symptoms 47-53 . One study found comparable reductions between the active and control groups 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven out the eight randomized controlled trials found that adding TMS on top of stable ongoing medications can reduce MDD symptoms. [47][48][49][50][51][52][53] One study found comparable reductions between the active and control groups. 54 The eight open-label studies found MDD symptom reductions of 15.4% to 63.3%, with an average of 50.8%.…”
Section: Tms and Psychotropic Medicationsmentioning
confidence: 99%
“…Interestingly, smaller doses of lisdexamfetamine/dextroamphetamine correlated with better rTMS outcomes. Despite promising results, the authors cautioned that the study's small sample size, limited data on psychostimulant use duration, and the lack of causal evidence necessitate further trials for solidifying the safety and efficacy of combining psychostimulants with rTMS (Wilke et al, 2022).…”
Section: Results Rtms In Depressionmentioning
confidence: 99%